1988
DOI: 10.1136/ard.47.11.886
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity to link protein in patients with inflammatory joint disease, osteoarthritis, and in non-arthritic controls.

Abstract: SUMMARY Cartilage link protein of high purity was prepared and used in an enzyme linked immunosorbent assay (ELISA). Antibodies to link protein were sought in the sera of 98 patients with rheumatic disorders; 38 with rheumatoid arthritis (RA), 29 with osteoarthritis (OA), 13 with psoriatic arthritis (PA), nine with ankylosing spondylitis (AS), nine with systemic lupus erythematosus (SLE), and in 83 healthy controls. Antibodies were detected in all groups with the following prevalences: 21/83 normals, 9/38 RA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…27 In the present study we have shown that a greater proportion of RA patients have peripheral blood derived T cells reactive to link protein (defined as an SI of 1.5 or greater) than non-arthritic individuals. The frequency of such responses was greater still in synovial fluid derived T cells.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…27 In the present study we have shown that a greater proportion of RA patients have peripheral blood derived T cells reactive to link protein (defined as an SI of 1.5 or greater) than non-arthritic individuals. The frequency of such responses was greater still in synovial fluid derived T cells.…”
Section: Discussionmentioning
confidence: 47%
“…ANTIGENS Link protein was purified as previously described. 27 Briefly, macroscopically normal human articular cartilage obtained from patients who had undergone total hip or knee replacement was minced and extracted with 4 molll guanidine hydrochloride (GuHCl). The extract was then fractionated by associative, followed by dissociative, caesium chloride density gradient centrifugation.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…Recently, we and other investigators have identified the involvement of humoral immunity in OA, including the presence of autoantibodies against cartilage components (24, 80–82). Mollenhauer et al (81) demonstrated elevated titers of autoantibodies against chondrocyte membrane proteins, and we (22, 24) found such a response to the cartilage matrix accessory proteins cartilage intermediate layer protein and osteopontin in OA patients.…”
Section: Autoimmunity To Cartilage Components In Oamentioning
confidence: 99%
“…Mollenhauer et al (81) demonstrated elevated titers of autoantibodies against chondrocyte membrane proteins, and we (22, 24) found such a response to the cartilage matrix accessory proteins cartilage intermediate layer protein and osteopontin in OA patients. Austin et al (82) detected serum antibodies to proteoglycan link protein in 26% of OA patients. Other investigators have identified antibodies to collagen in synovial fluids from OA patients and from animal models of OA (3, 83, 84).…”
Section: Autoimmunity To Cartilage Components In Oamentioning
confidence: 99%